Heterogeneous associative plasticity in the auditory cortex induced by fear learning - novel insight into the classical conditioning paradigm - Zelenka, O; Novak, O; Brunova, A; Syka, J (Physiological research, 2021)
We used two-photon calcium imaging with single-cell and cell-type resolution. Fear conditioning induced heterogeneous tuning shifts at single-cell level in the auditory cortex, with shifts both to CS+ frequency and to the control CS- stimulus frequency. We thus extend the view of simple expansion of CS+ tuned regions. Instead of conventional freezing reactions only, we observe selective orienting responses towards the conditioned stimuli. The orienting responses were often followed by escape behavior.
Keywords: učení; Behavior, Animal; Interneurons; Male; strach; sluchové korové centrum; Fear; mužské pohlaví; interneurony; Neuronal Plasticity; akustická stimulace; Learning; Animals; Auditory Cortex; Electroshock; zvířata; Conditioning, Classical; Acoustic Stimulation; myši inbrední C57BL; myši; chování zvířat; Mice, Inbred C57BL; klasické podmiňování; elektrický šok; Mice; neuroplasticita